Jumlah Tanaman Per Lubang Tanam Terhadap Pertumbuhan Dan Produksi Tanaman Pakcoy (Brassica oleraceae) Pada Penanaman Sistem Hidroponik NFT - Jamaludin Jamaludin; Maryati Maryati; M. Gary Ranchiano (JURNAL WACANA PERTANIAN, 2018)
This research aimed to find out the effect of the number of plants per hole on the growth and yield of hydroponic pakcoy plants. The study was carried out in the STIPER Dharma Wacana Metro greenhouse from May to June 2018. The treatments tested were one plant, two plants, three plants, and four plants per hole. The hydroponic system used is the Nutrient Film Technique (NFT) system. The variables observed were plant height, number of leaves, widest leaves, stem diameter, total plant weight, and root weight. The results showed that the treatment of one plant per hole produced better growth than other treatments with plant height of 23.65 cm, number of leaves 12.1 strands, crop diameter 5.59 cm, and longest root 38.25 cm.